Peran Badan Permusyawaratan Desa Dalam Perencanaan Pembagunan Desa Di Desa Mamuya Kecamatan Galela Kabupaten Halmahera Utara - Kansige, Enggelion; Pangkey, Masje Silija; Pombengi, Jericho Denga (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract : In the village development community participation is needed, the public participation can takethe form of active participation means that people are willing to carry out development programs in theplanning, implementation and utilization of development. Aspirations of the people can be accommodatedthrough the Village Consultative Body (BPD) in the development planning. Because basically they wereaccommodating and channel the aspirations of the people it represents.The method used in this research is descriptive qualitative method. Informants were taken from variousrelated elements, namely the head of the village, kaur pembagunan, BPD, public and community stores.Wawancar data collection technique. The analysis technique used is qualitative analysis.Of the existing research, the role of the village consultative bodies in the village have not been fullyincluded pembagunan planning go well because in this case a lot of complaints from people who do notteratasi.BPD in making decisions in the village is not in accordance with the interests of the people in thevillage, but they simply take its own policy without involving masyaraka.Keywords. Role Village Consultative Body, Planning pembagunan Village.